On the invertibility of one integral operator - Kirakosyan, Grigor (Armenian Journal of Mathematics, 2022)
The present paper considers an integral operator defined on the entire real axis, which differs from the Hilbert transform with terms where kernels are constructed using integral exponential functions. The considered operator has similar properties with respect to the Hilbert transform. The form of the inverse operator is obtained.